Measurement of the CP-violating phase ϕs in B[bar]0s→D+sD−s decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2014)
We present a measurement of the CP-violating weak mixing phase ϕs using the decay ¯B0s→D+sD−s in a data sample corresponding to 3.0 fb−1 of integrated luminosity collected with the LHCb detector in pp collisions at center-of-mass energies of 7 and 8 TeV. An analysis of the time evolution of the system, which does not use the constraint |λ|=1 to allow for the presence of CP violation in decay, yields ϕs=0.02±0.17(stat)±0.02(syst) rad, |λ|=0.91+0.18−0.15(stat)±0.02(syst). This result is consistent with the standard model expectation.